Are Graduate Students with Disabilities Seen? A Study of Canadian University Websites, Policies, and Faculty Training Materials - Parsons, Jeanette; Parsons, Samantha; Bryden, Pamela; Fletcher, Paula (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur, 2025)
Despite a national task force recommending policy reforms nearly a decade ago to improve inclusion, increased enrolment, and evolving legislation, the visibility of graduate students within Canadian universities remains limited. This study examined the websites of 55 Canadian universities, their accommodation policies for students with disabilities, and publicly available training resources for graduate faculty. Findings showed that graduate students with disabilities are largely absent from these institutional narratives. Notably, the scope, intent, and rationale behind the accommodation policies varied significantly, indicating a lack of consistency across institutions, which may hinder equitable access and support. The study highlights the need for coordinated efforts among student affairs professionals, graduate faculties, and equity, diversity, and inclusion units to enhance visibility and inclusion of graduate students in higher education.